Single channel seismic reflection processed data (GI Gun entire dataset) of RV SONNE during cruise SO240 - Heinrich Villinger; Norbert Kaul; Thomas Kuhn; Arne Schwab (PANGAEA, 2024)
The research cruise SO-240 took place from May 3rd, 2015 until June 16th, 2015 at about 12° N and 118° W, approximately 900 nm offshore Mexico in the equatorial NE Pacific. This cruise started and ended in the port of Manzanillo on the west coast of Mexico. During the cruise a total of 636 km of single channel seismic data (SCS) were acquired on 18 profiles. For seismic signal generation a single GI gun was used with a volume of 3.4 liter. Data were acquired with a 101 m active length streamer with 16 channels. Details of the recording system can be found in Kuhn (2015). The recorded data were processes with VISTA. All 16 channels were binned, stacked, band-pass filtered (Ormsby 10/15 - 80/90) and time migrated with a sound velocity of 1500 m/s.